Ketika Jalanan Bicara: Gerakan Protes 2025 di ASEAN dan Nepal dalam Perspektif Hukum Internasional dan Geopolitik - Alfianty Dara (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2026)
The wave of social protests that swept across Asia in 2025 represents a new dynamic in the relationship between the state, citizens, and international law. This study analyzes protest movements in five countries—Indonesia, the Philippines, Vietnam, Timor-Leste, and Nepal focusing on the extent to which government responses align with the principles of the International Covenant on Civil and Political Rights (ICCPR) and their connection to regional geopolitical dynamics. Employing a comparative qualitative approach within a juridical, sociological, and geopolitical framework, the research assesses each country’s level of compliance with ICCPR Articles 19 and 21 using the UN Human Rights Committee’s General Comment No. 37 as the analytical reference, and a three-level compliance scale (high, moderate, low). Data were derived from international organization reports, global media sources, and legal documents. The findings indicate that the 2025 Asian protests were driven by a combination of economic inequality, political corruption, and restrictions on freedom of expression. Indonesia and Nepal exhibited high levels of repression, while Timor-Leste demonstrated a more open model of social dialogue. From a geopolitical perspective, transnational solidarity emerged through digital campaigns and cross-border activist networks, reflecting the rise of digital resistance in Asia. The study concludes that state legitimacy in the region is increasingly tested not only by domestic stability but also by the capacity to uphold international norms amid shifting global power structures and digital transformations.